The efficacy of polyether‐ether‐ketone wire as a retainer following orthodontic treatment - Ammar Salim Kadhum; Akram Faisal Alhuwaizi (Wiley, 2021)
Abstract Objectives To investigate the efficacy of polyether‐ether‐ketone (PEEK) wire as a fixed orthodontic retainer, by comparing its performance to other retainer wires and optimizing its adhesion to composite bonding materials. Materials and methods Retainer wires of 15 mm segments were used, PEEK wires were prepared in cylindrical form with 0.8 mm diameter, and had two surface treatments namely air‐abrasion and conditioning with adhesive system. Three different metallic retainer wires were used for comparison and three tests were performed; two tests measured debonding force and associated wire deflection from acrylic blocks and bovine teeth and one test for pull‐out force. To test debonding force, a vertically directed compressive force was applied to the retainer wires bonded to the acrylic blocks and bovine teeth, while for pull‐out test; a vertically directed tensile force detached the retainer wire. Results In both debonding tests, PEEK wires (regardless the surface treatment) had non‐significant difference when compared to each other, or to the other metallic wires, except the dead‐soft coaxial wire group. The dead‐soft coaxial wire group had significant difference when compared to other groups regarding both the force magnitude and maximum deflection, the only exception was the debonding force of the flat braided retainer wires bonded to bovine teeth. In pull‐out test PEEK wires conditioned with adhesive system and the air‐abraded recorded the second and third highest readings respectively. Conclusions Within the limitations of this study, the 0.8 mm round PEEK wires have comparable performance-in terms of debonding and pull out forces-to conventional retainers when bonded with 4 mm composite bonding spots; using air‐abrasion for 10 s at 3.5 MPa provided sufficient adhesion of the composite to the wire, and conditioning with adhesive system may provide no further clinical benefit.